2023
DOI: 10.1111/jwas.12959
|View full text |Cite
|
Sign up to set email alerts
|

Humanizing aquaculture development: Putting social and human concerns at the center of future aquaculture development

Abstract: Compared with other aquaculture issues, attention to human and social dimensions is lagging behind. Sectoral development, policy, and programmatic factors have created inequities and sub‐optimal social outcomes, which are jeopardizing the broader contribution the sector could make to human well‐being. Human rights in aquaculture are at the core of this article, which argues that aquaculture development, as a major economic and food producing sector, needs to be about human development. The article reviews: the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…When locally caught forage fish are used for industrial purposes, they are often exported as feed for high-value farmed species instead of being utilized for human consumption in the area. The "practice" raises questions about fairness and socioeconomic justice, particularly concerning its effect on the local communities' economics and nutrition [21,22].…”
Section: Socioeconomic Questionmentioning
confidence: 99%
“…When locally caught forage fish are used for industrial purposes, they are often exported as feed for high-value farmed species instead of being utilized for human consumption in the area. The "practice" raises questions about fairness and socioeconomic justice, particularly concerning its effect on the local communities' economics and nutrition [21,22].…”
Section: Socioeconomic Questionmentioning
confidence: 99%
“…Gender data is often not detailed, especially regarding casual work, which is common in aquaculture and fisheries production/processing. It remains a challenge to show the visibility of women's participation in aquaculture (as a starting point to progressing towards gender equality in the sector) (Brugere & Williams, 2017). The biannual questionnaire sent by FAO to its member countries to monitor the implementation of the 1995 Code of Conduct for Responsible Fisheries (within which Article 9 is on aquaculture) does not include any questions on gender—which is not surprising given the Code itself is gender‐blind (Williams, 2016).…”
Section: Increasing Aquaculture's Positive Contribution To the Sdgs—c...mentioning
confidence: 99%
“…Transdisciplinary assessments of both fed and unfed aquaculture systems have shown that many types of aquaculture systems produce products of higher nutritional values and altogether aquaculture accounted for less than 1% of anthropogenic greenhouse gas (GHG) emissions in 2017, similar to emissions from sheep production (Gephart et al, 2016(Gephart et al, , 2021Hallström et al, 2019;MacLeod et al, 2020). However, significant socio-cultural inequities lead to food justice inequality and consequently political opposition to aquaculture exists, which poses serious obstacles to its expansion and growth (Brugere et al, 2023;Carter, 2018;Krause et al, 2015).…”
Section: The Role Of Aquaculture In Sustainable Development and Globa...mentioning
confidence: 99%